La cognición: el punto de vista neurológico - Trelles, Luis (1986)
The authors review from an historical perspective different ways of concieving the cognitive processes. Then they analize the role played by severa! nervous structures in relationship to cognition. Finally they explain dimensions of cognitive processes linking them to neurological research.